The relationship between back squat strength and sprint times among male NCAA track athletes - Conan, R.; DeBeliso, M. (International Journal of Sports Science, 2020)
Prior research indicates that lower body strength and body mass are associated with athletic performance including sprint speed [1,2]. The direct association between lower body strength and track competition sprint performance has not been well documented. Hence, the purpose of this study was to determine if there was a meaningful relationship between relative strength in the back squat (BSQ) and 60-100m competition sprint times among male college sprinters. The participants were male NCAA Division 1 track sprinters 18-21 years of age (n = 16). Data collected from each athlete included 1-RM BSQ (kg), Body mass (kg), 60m, and 100m sprint times. BSQ, BSQ/Body Mass, and allometrically scaled BSQ/(Body Mass**0.67) scores were then compared to the 60m and 100m sprint times using the Pearson correlation coefficients (r). Results demonstrated moderate to high negative relationships between 60m sprint times and BSQ metrics ranging from r= -0.55 to -0.62 (p<0.05). The relationships between 100m sprint times and BSQ metrics ranged from low negative r=-0.32 (non-significant p>0.05) to moderate negative r=-0.57 (significant p<0.05). Within the parameters of this study, 60m sprint times are meaningfully associated with relative lower body strength, while relative lower body strength is less of a factor in regards to the 100m sprint times.